2010
DOI: 10.1044/1058-0360(2009/08-0036)
|View full text |Cite
|
Sign up to set email alerts
|

Early-, Middle-, and Late-Developing Sounds in Monolingual and Bilingual Children: An Exploratory Investigation

Abstract: These exploratory findings indicate the need for longitudinal examination of EML categories with a larger cohort of children to observe similarities and differences between monolingual and bilingual development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 36 publications
5
58
0
Order By: Relevance
“…Kathryn's Spanish productions also displayed a quite advanced repertoire of Spanish consonants. Only the flap and the velar voiceless fricative [x] were in the targets but were never accurately reproduced, in line with the common finding that these sounds appear quite late even in monolinguals (Fabiano-Smith & Goldstein, 2010a Taken together, these findings suggest that Kathryn's emerging phonological systems were differentiated from the earliest stages of production. Her ability to match the various gestural properties of word-initial segments and the types of errors she produced varied across languages, indicating that she was at distinct stages of phonological development in each language.…”
Section: Resultssupporting
confidence: 69%
“…Kathryn's Spanish productions also displayed a quite advanced repertoire of Spanish consonants. Only the flap and the velar voiceless fricative [x] were in the targets but were never accurately reproduced, in line with the common finding that these sounds appear quite late even in monolinguals (Fabiano-Smith & Goldstein, 2010a Taken together, these findings suggest that Kathryn's emerging phonological systems were differentiated from the earliest stages of production. Her ability to match the various gestural properties of word-initial segments and the types of errors she produced varied across languages, indicating that she was at distinct stages of phonological development in each language.…”
Section: Resultssupporting
confidence: 69%
“…the use of a language-specific structure in a production of the other language; Lleó & Rakow, 2005, 2006bParadis, 2001). Some studies have found differences in the order of acquisition of speech sounds in bilingual children as compared to their monolingual peers (Fabiano-Smith & Goldstein, 2010a;Lleó & Rakow, 2006b). A similar rate of acquisition between monolinguals and bilinguals has also been observed on the production of some phonological structures (e.g.…”
Section: Studies Of Speech Productionmentioning
confidence: 94%
“…a faster rate of production when compared to monolingual peers; Lleó, Kuchenbrandt, Kehoe, & Trujillo, 2003), (2) deceleration (i.e. a slower rate of acquisition as compared to their monolingual peers; Fabiano-Smith & Goldstein, 2010a;Lleó & Rakow, 2005) and (3) transfer (i.e. the use of a language-specific structure in a production of the other language; Lleó & Rakow, 2005, 2006bParadis, 2001).…”
Section: Studies Of Speech Productionmentioning
confidence: 98%
“…In general, investigation of phonological development in ELLs has indicated that even though bilingual speakers are acquiring two phonological systems, consonant and vowel accuracy in typically developing bilingual children is similar but not identical to that of monolingual children (e.g., Bunta, Fabiano-Smith, Goldstein, & Ingram, 2009;Fabiano-Smith & Goldstein, 2010;Goldstein, Fabiano, & Washington, 2005). Bunta et al (2009) and reported that 3-and 4-year-old bilingual Spanish-English speakers had consonant accuracy in English (PCC) that was slightly lower for bilingual than monolingual children.…”
Section: Vowel and Consonant Accuracymentioning
confidence: 97%